External Actor Involvement in Myanmar Conflict Negotiations: China’s Mediation with the Three Brotherhood Alliance Post-Coup 2021 - Wahyu Dwi Pambagyo; Mohammad Aras Al Rasyid; Ahmad Sahide (Indonesian Journal of Multidisciplinary Sciences (IJoMS), 2026)
This study aims to analyze China’s role as an external mediator in the Myanmar conflict following the 2021 military coup and the military operations of the Three Brothers Alliance. The study examines China’s transformation from a policy of non-intervention to active diplomatic engagement and its impact on regional stability. The theoretical framework used is mediation theory, specifically Zartman's concept of Mutually Hurting Stalemate (MHS), which explains that effective mediation occurs when the conflicting parties recognize the losses caused by the continuation of the conflict and are motivated to negotiate. This theoretical framework helps to understand China’s mediation strategy in facilitating dialogue amid the complex political and military stalemate in Myanmar. This study uses a qualitative library research method by analyzing secondary data from academic journals, policy reports, and reliable media sources such as The Irrawaddy, Reuters, and Al Jazeera. Thematic analysis is applied to identify patterns of China’s diplomatic, military, and economic involvement. The main findings reveal that China’s military and economic support has strengthened the political legitimacy of Myanmar's military junta, increased Myanmar's economic dependence on China’s, and exacerbated tensions with ethnic groups in Myanmar. Regionally, China’s influence has deepened divisions within ASEAN, affected relations with India, and heightened security tensions in the region.